Gravity redux: Measuring international trade costs with panel data - Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2011)
Barriers to international trade are known to be large but due to data limitations it is hard to measure them directly for a large number of countries over many years. To address this problem I derive a micro-founded measure of bilateral trade costs that indirectly infers trade frictions from observable trade data. I show that this trade cost measure is consistent with a broad range of leading trade theories including Ricardian and heterogeneous firms models. In an application I show that U.S. trade costs with major trading partners declined on average by about 40 percent between 1970 and 2000, with Mexico and Canada experiencing the biggest reductions.
Keywords: F10; F15; 330; trade costs; gravity; multilateral resistance; Ricardian trade; heterogeneous firms